Identification of small molecule modulators of HIV-1 Tat and Rev protein accumulation. Issue 1 (December 2017) - Balachandran, Ahalya; Wong, Raymond; Stoilov, Peter; Pan, Sandy; Blencowe, Benjamin; Cheung, Peter; Harrigan, P.; Cochrane, Alan
Abstract Background HIV-1 replication is critically dependent upon controlled processing of its RNA and the activities provided by its encoded regulatory factors Tat and Rev. A screen of small molecule modulators of RNA processing identified several which inhibited virus gene expression, affecting both relative abundance of specific HIV-1 RNAs and the levels of Tat and Rev proteins. Results The screen for small molecules modulators of HIV-1 gene expression at the post-transcriptional level identified three (a pyrimidin-7-amine, biphenylcarboxamide, and benzohydrazide, designated 791, 833, and 892, respectively) that not only reduce expression of HIV-1 Gag and Env and alter the accumulation of viral RNAs, but also dramatically decrease Tat and Rev levels. Analyses of viral RNA levels by qRTPCR and RTPCR indicated that the loss of either protein could not be attributed to changes in abundance of the mRNAs encoding these factors. However, addition of the proteasome inhibitor MG132 did result in significant restoration of Tat expression, indicating that the compounds are affecting Tat synthesis and/or degradation. Tests in the context of replicating HIV-1 in PBMCs confirmed that 791 significantly reduced virus replication. Parallel analyses of the effect of the compounds on host gene expression revealed only minor changes in either mRNA abundance or alternative splicing. Subsequent tests suggest that 791 may function by reducing levels of the Tat/Rev chaperone Nap1. Conclusions The three compounds examined (791, 833, 892), despite their lack of structural similarity, all suppressed HIV-1 gene expression by preventing accumulation of two key HIV-1 regulatory factors, Tat and Rev. These findings demonstrate that selective disruption of HIV-1 gene expression can be achieved.